2013
DOI: 10.3109/09286586.2012.746994
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Causes of Visual Impairment and Blindness, Cataract Surgical Coverage and Outcomes of Cataract Surgery in Libya

Abstract: Libya needs to improve the quality of cataract surgery across all the regions. The southern region needs improvement in both quality and coverage of services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…Although the RAAB survey includes questions on barriers to cataract surgery not all publications report these findings. Among the 12 published RAAB surveys 2 3 4 5 6 7 8 9 10 11 12 13 , data on barriers to cataract surgery were only available in 9 articles. 2 3 4 5 6 7 8 9 10 Among these publications 23 24 25 26 27 the outcomes varied considerably [ Table 1 ].…”
Section: Resultsmentioning
confidence: 99%
“…Although the RAAB survey includes questions on barriers to cataract surgery not all publications report these findings. Among the 12 published RAAB surveys 2 3 4 5 6 7 8 9 10 11 12 13 , data on barriers to cataract surgery were only available in 9 articles. 2 3 4 5 6 7 8 9 10 Among these publications 23 24 25 26 27 the outcomes varied considerably [ Table 1 ].…”
Section: Resultsmentioning
confidence: 99%
“…A similar explanation was preferred for corneal opacity as a major cause of blindness in parts of Libya. 18 …”
Section: Discussionmentioning
confidence: 99%
“…In Irbid, Jordan, 11 posterior segment disease (aside from previously mentioned diseases) was responsible for 10% of blindness; it was 10.9% in Moldova, 12 and 16% in Chiapas, Mexico. 7 Although globally, glaucoma is showing a trend to be the third major cause worldwide, 18 it is the fourth major cause of blindness in Jazan (5.2%) as the high prevalence of corneal scar had displaced it to the third position. However, as with international trends, glaucoma tends to be ranked as the second or third major cause in other similar studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although other studies have implemented some form of remoteness stratification, most have considered remoteness as an urban–rural dichotomy . The majority of studies, both in Australia and globally, have not reported stratifying by remoteness at all, have only controlled for remoteness through design effect calculations or retrospectively adjusted for remoteness during analysis . The ARIA+ system used in the NEHS assigns a remoteness score to all SAs as a function of road distance to the nearest major service centre (including health service centres).…”
Section: Discussionmentioning
confidence: 99%